Histoenzymic study on parotid salivary gland of castrated donkey - SINGH, JASWANT; PAWAR, HARCHARAN SINGH; ROY, K S (The Indian Journal of Animal Sciences, 2013)
Histoenzymic study was made on parotid salivary glands of castrated donkeys. The mucous and serous acinar cells were positive for AKPase, ACPase, ATPase, AChEase, SDH, LDH, GDH, G6PD, CYO, MAO and NADPH-diaphorase. Myoepithelial cells had better demonstrable oxidoreductases and ATPase, The acinar cells and ductular epithelium were also positive for sudanophilic lipid. The striated and large ducts exhibited strong to intense activity for oxidoreductases and were considered more physiologically active components of the parotid salivary gland.